DINASTI POLITIK PADA PILKADA 2020 DI JAWA TIMUR DARI PERSPEKTIF RATIONAL CHOICE - Yunita Ratna Sari (Universitas Islam Darul Ulum Lamongan, 2022)
Political dynasties have occurred in regional head elections, one of which is in East Java. The form of kinship in regional head elections in East Java, namely from children, wives, nieces and younger siblings. This research uses literature study. The results of the study indicate that the superiority of dynastic politics are make it easier for candidates to get the most vote and the disadvantages of closing the participation space for candidates who do not have kinship with the political elite.